Agricultural dust explosions in 2008 - Ambrose, R. P. Kingsly (Kansas State University. Dept. of Grain Science and Industry, 2015)
There were 19 dust explosions reported in the U.S. in 2008 according to Kingsly Ambrose, Assistant Professor, Kansas State University. This compares to 7 in 2007 and a ten-year average of 9.4 explosions.
Keywords: Grain dust; Dust explosions